A giant vascular hamartoma of the breast in a child. - Deshmukh H (Journal of Postgraduate Medicine, 1997)
Vascular tumors of the breast are uncommon. Perilobular hemangiomas, the commonest histologic subtype of breast hemangiomas, constitute majority of microscopic, vascular mammary tumors. Macroscopic hemangiomas and vascular hamartomas of the breast are distinctly rare. We describe a giant, vascular hamartoma of the right breast in a five year old girl and discuss pertinent literature.